Bi-directional DC–DC Converter with Adaptive Fuzzy Logic Controller - Rajarajeswari, N.; Thanushkodi, Dr.K. (Elektronika ir Elektrotechnika, 2009)
A bi-directional DC-DC converter with adaptive fuzzy logic controller (AFLC) is introduced. Bi-directional power flow is obtained by the same power components and provides a simple, efficient, and galvanically isolated converter. In the presence of DC mains the converter operates as buck converter, powers the down stream converter and also charges the battery. When the DC mains fails, the converter operates as boost converter and the down stream converters are fed by battery. In both the modes the power switches are controlled by PWM technique and the pulses are generated by application fuzzy logic with an adoption algorithm. The proposed converter is simulated using MATLAB and laboratory prototype is developed to validate the simulation results. Ill. 9, bibl. 11 (in English; summaries in English, Russian and Lithuanian).